Metaphysics of Wayang Tauhid Play 'Wedhare Sadat Tembayat' Presented by Ki Sunardi Wirocarito - Luwiyanto; Syamsuddin, M. Mukhtasar; Lasiyo (Program Studi Sastra Jawa, Fakultas Bahasa dan Seni, Universitas Negeri Semarang, 2025)
Wayang has a closeness to the behavior and mindset of Javanese people. It is believed that there is a broad and deep philosophical thought system. The wayang performance, character, or nature of the wayang figures conveys the intellectual values ​​of life. Each character comes from a reflection or representation of humans' attitude, character, and nature. Wayang Tauhid, the play Wedhare Sadat Tembayat, which is full of the delivery of philosophical values, is the object of this research. Based on the material object's characteristics, the study focuses on the metaphysical approach. How can humans reveal reality's most profound meaning through metaphysical studies and explanations. The purpose of this study and explanation is to open the way for humans to gain knowledge of the actual reality, namely the existence of Allah. This study is included in qualitative research in the realm of library research. Because the material object is philosophy, this study uses the hermeneutic philosophical method. The hermeneutic philosophical method provides a comprehensive and in-depth approach to studying philosophy. From a metaphysical perspective, the study's results indicate that the WST play has an existential orientation, suggesting that humans have material, emotional, and spiritual limitations. The WST play teaches humans to live based on the oneness of Allah, the True Being. Everything in the world is an event, as a being that does not exist, is only created by Allah, the True Being. This reminds humans that life in the world is only temporary and has limits, so life should not chase worldly things too much, but carry out human obligations to get closer to Allah through faithful prayer. This statement shows that the metaphysics of the WST play is monistic and spiritual.